The Van Hiele model and the teaching of the geometry - Vargas Vargas, Gilberto (2013)
This article discusses the application of the model of Van Hiele geometric reasoning and the teaching of geometry. It reflects on the importance of studying geometry and what this means for modern society, analyzing also the conceptions and difficulties that exist in the form of teaching and learning geometry. Introduce the Van Hiele model explaining the evolution of geometric reasoning through five consecutive levels and the support given, by its five stages, to the organization of the curriculum and a comparison with the development theory of Piaget.